Africanities, Mathematics and Mamulengos Theater: a crossroads of knowledge and reflections (Revista Internacional de Formação de Professores, 2023)
This article aims to discuss about ancestry and orality as dimensions of africanities in a theatrical proposal that articulates, through the Mamulengos Theater, afrodiasporic wisdoms and the valorization of the african mathematical legacy. We analyze Narrative Excerpts of the theatrical performance entitled MatemÁfrica: roots of the flight of Sankofa and the power of Boi-Bumbá. In this sense, we highlight the crossroads and cross-crossings as potentializers of other proposals in the field of Mathematics Education. The notion of crossings guides the discussions in this text, enabling decolonial perspectives that tension mathematics and its teaching, as well as the training of teachers who teach mathematics. The narrative excerpts reveal that such wisdoms can contribute to the teaching of mathematics in an anti-racist perspective, whether in the discussion of the origins of mathematics and mathematical artifacts produced in Africa, whether in the Mamulengos Theater as a form of resistance originated on the floor of the senzalas, whether in the recognition of science produced in the oral culture of ancestral wisdoms.
Keywords: Ancestrality. Orality. Mamulengos' theatre. African mathematics.